A defective phage system reveals bacteriophage T4 replication origins that coincide with recombination hot spots. - Kreuzer, K N (1985)
Plasmid transduction mediated by bacteriophage T4 has been used to study putative T4 DNA replication origins cloned as inserts in the Escherichia coli plasmid pBR322. Two particular inserts from the T4 genome allow high-frequency plasmid transduction, suggesting that each insert might contain a T4 replication origin. T4 infection of these plasmid-containing cells produces large numbers of defective phage particles that contain long linear concatamers of the plasmid DNA. During a second cycle of infection, these defective phage genomes can be replicated better than normal phage chromosomes present in the same infected cell; consequently, the T4 DNA inserts must be functioning as replication origins. Both of these origins appear to utilize a previously unrecognized mode of T4 replication initiation. Moreover, each origin coincides with a major recombination hot spot in the phage genome, and therefore this mode of replication initiation seems to involve a local stimulation of homologous genetic recombination. From a purely practical standpoint, additional DNA fragments can be cloned in an origin-containing plasmid, allowing isolation of large amounts of any DNA sequence with the glucosylated hydroxymethylcytosine modifications of T4 DNA.